Use of helicopter emergency medical services with a physician on board in severe pediatric trauma in Korea: a case report - Yoonsuk Lee; Gunwoo Kim; Pil Young Jung (Journal of Trauma and Injury)
In Korea, helicopter emergency medical services (HEMS) with a physician on board were introduced in September 2011, funded by both central and regional governments. HEMS was integrated into the Korean emergency medical system to address the need for EMS in remote rural areas. The present report describes 16-month-old twins who fell from the fifth floor of an apartment building, located approximately 100 km from the nearest level I trauma center. Utilizing HEMS along with initial emergency management by an emergency physician, the patients were transported to the level I trauma center within the critical “golden hour.” The children had sustained multiorgan injuries. Without intervention at the scene by an emergency physician, a fatal outcome was anticipated for both children. With the use of HEMS, one patient died, but the other survived with a good prognosis. The use of HEMS flights with an emergency physician on board may improve outcomes for pediatric patients with severe trauma in medically underserved rural areas.